ANALISIS KOMPREHENSIF KELAYAKAN BISNIS BRAND KOPI KENANGAN PODOMORO CITY MEDAN MENGGUNAKAN PENDEKATAN 8 ASPEK STUDI KELAYAKAN - Sariyani Sariyani; Kia Napisa Siregar; Muhammad Fahri; M. Khadafi Harza; Dini Vientiany (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the business feasibility of kopi kenangan podomoro city medan branch using an eight-aspect business feasibility approach, including market and marketing, legal, technical and operational, management, financial, sharia compliance, socio-economic, and environmental aspects. The research employed a descriptive qualitative approach, with data collected through direct observation and a mini-survey involving 50 respondents consisting of students, office workers, and surrounding communities. The results indicate that from a market perspective, kopi kenangan shows a high level of consumer purchase interest supported by effective digital marketing strategies and a strategic business location. From legal and sharia aspects, the business complies with regulatory requirements and holds halal certification. Financial analysis reveals that the business is financially feasible, with a return on investment (roi) of 131% and a payback period of approximately 9–12 months. Furthermore, the business contributes positively to social and environmental aspects through job creation, the use of local raw materials, and responsible waste management. Therefore, kopi kenangan podomoro city medan is considered feasible and has strong prospects for sustainable business development.